Incidence and clinical features of post-injection endophthalmitis according to diagnosis. Issue 8 (19th November 2015) - Rayess, Nadim; Rahimy, Ehsan; Shah, Chirag P; Wolfe, Jeremy D; Chen, Eric; DeCroos, Francis C; Storey, Philip; Garg, Sunir J; Hsu, Jason
Abstract : Purpose: To compare the incidence and clinical features of endophthalmitis after intravitreal antivascular endothelial growth factor (VEGF) therapy for diabetic eye disease, neovascular age-related macular degeneration (AMD) and retinal vein occlusion (RVO). Methods: Multicentre, retrospective, consecutive case–control study. All patients treated with intravitreal bevacizumab, ranibizumab or aflibercept for diabetic eye disease, neovascular AMD or RVO between 1 January 2009 and 30 September 2013 at three retina practices were included in this study. The total number of anti-VEGF injections administered for the three indications was calculated using billing records. Endophthalmitis cases were identified using both endophthalmitis log sheets and billing records. Patient charts were reviewed to confirm that endophthalmitis was directly related to anti-VEGF injection and to record clinical features and culture results. Results: During the study period, a total of 353 978 intravitreal anti-VEGF injections were performed. Presumed infectious endophthalmitis occurred in 119 of 296 017 injections performed for neovascular AMD (1/2487, 0.040%), 12 of 24 541 for diabetic eye disease (1/2045, 0.049%) and 4 of 32 418 for RVO (1/8104, 0.012%). χ 2 analysis found endophthalmitis rates to be higher in diabetic eye disease compared with RVO (p =0.010) and higher in neovascular AMD compared with RVO (p=0.014), while diabetic eye disease and neovascular AMD (p=0.517) had similar rates. The average age of the overall neovascular AMD patient population (81.9 years) was significantly older than the diabetic eye disease (64.7 years, p<0.001) and RVO (73.4 years, p<0.001) populations. Conclusions: Endophthalmitis rates appear to be lower in eyes with RVO compared with diabetic eye disease and neovascular AMD, possibly due to impaired immunity in diabetics and waning immunity in the generally older AMD population.